2007
DOI: 10.1007/s00784-007-0167-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the effect of ultrasonic instruments on the root surface in vivo

Abstract: The present study was designed to investigate the effectiveness of different ultrasonic instruments on the root surface. Fourteen patients with 35 single root teeth designated for extraction were recruited to the present study. Teeth were assigned to four experimental groups: group 1, piezoelectric ultrasonic device; group 2, magnetostrictive ultrasonic device; group 3, hand instrumentation; and group 4, untreated teeth (control). After instrumentation, the teeth were extracted and the presence of residual dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
43
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 31 publications
6
43
3
1
Order By: Relevance
“…Only the comparison between the C200 and P200 groups was significant. In contrast to our study, Santos et al [13] showed that under SEM, there were no differences between the results of the magnetostrictive and piezoelectric devices. The main reasons for such differences are the methodology used such as an in vitro or in vivo study, the use of different tips, the power setting, and the time and load of the instrument.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Only the comparison between the C200 and P200 groups was significant. In contrast to our study, Santos et al [13] showed that under SEM, there were no differences between the results of the magnetostrictive and piezoelectric devices. The main reasons for such differences are the methodology used such as an in vitro or in vivo study, the use of different tips, the power setting, and the time and load of the instrument.…”
Section: Discussioncontrasting
confidence: 99%
“…The relationship between the force and defect volume caused by ultrasonic instruments was confirmed by Flemming et al [12], and in this study we chose ultrasonic application forces of 100 g and 200 g. By controlling the force, the relationship between the force and tooth roughness could be evaluated using a digital pressure sensitive device [13]. A SEM was used to evaluate the tooth roughness.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast with other studies that compared standard area‐specific curets versus standard tip mounted on machine‐driven instruments and that showed that curets can create deep grooves and remove sound tooth substance from tooth surface when compared with machine‐driven instruments (Santos, Pochapski, Leal, Gimenes‐Sakima, & Marcantonio, ).…”
Section: Discussioncontrasting
confidence: 91%
“…Another study by Santos et al [26], however, contradicts these findings. This in vivo comparison found significantly rougher surfaces after hand curette treatment than after ultrasonic treatment.…”
Section: Discussionmentioning
confidence: 87%